Sulfur dioxide and benzo(a)pyrene trigger apoptotic and anti-apoptotic signals at different post-exposure times in mouse liver. (November 2015) - Qin, Guohua; Wu, Meiqiong; Sang, Nan
Highlights: SO2 and BaP trigger apoptotic and anti-apoptotic signals at different times. Mitochondrial dysfunction might be an initial event after SO2 and BaP co-exposure. P53 accumulation and phosphorylation take part in SO2 and BaP induced apoptosis. Anti-apoptotic signals are important to carcinogenic potential of SO2 and BaP. Abstract: There is considerable concern that exposure to PAHs in combination with other air pollutants may lead to cancer or apoptosis in different cells. This study investigated the interaction effects between SO2 and BaP in mouse liver after long-term exposure. Mice were exposed to BaP for 5 days or SO2 inhalation for 4 weeks alone or together. The mitochondrial membrane potential (MMP) was assessed using the lipophilic cationic probe JC-1. The mRNA and protein level of several mitochondrial respiratory complex subunits and apoptosis-related genes were analyzed by real-time RT-PCR and/or western blot, respectively. We observed the pathology change of the mouse liver after 4-week treatments. It was revealed that MMP was reduced after co-exposure of SO2 and BaP after a 4-week treatment (1 day post-exposure, p.e. 1 d), with the suppression of the mRNA expression of complexes IV and V subunits, CO1, CO4, and ATP6. Co-exposure of SO2 and BaP appeared to be able to cause apoptotic signals, as judged by the suppression of bcl-2 and the bcl-2/bax ratio and the elevation of bax, caspase 3 activation, p53 accumulation and phosphorylation 1 d post-exposure to SO2 and BaP, while the anti-apoptotic signal was detected by the elevation of bcl-2 and the bcl-2/bax ratio as well as the suppression of bax and p53 expression after a 13-week post-exposure (p.e. 13 w) of SO2 and BaP. These results indicate that co-exposure to SO2 and BaP appears to lead to apoptotic as well as anti-apoptotic signals at different post-exposure times.